Driving policy coherence and strengthening institutions to advance socio-ecological gains - Edward-Uwadiale, Regina (CGIAR System Organization, 2025)
The article highlights the CGIAR Multifunctional Landscapes Science Program’s efforts to work with partners across sub-national, national, and regional levels to align policies, co-generate evidence, and strengthen governance structures that support multifunctional land management. It describes analytical work on political economy and governance, science–policy dialogues, and institutional arrangements that enable sustainable practices to flourish beyond pilot sites. The piece also emphasizes breaking sectoral silos by linking agriculture, environment, and socio-economic development goals, and showcases examples of institutional innovations and policy uptake—such as multi-stakeholder platforms and adaptive governance models—that foster inclusive, effective decision-making. Overall, the article illustrates how coordinated policy and institutional frameworks can create enabling environments for sustainable landscape transformation, ultimately contributing to biodiversity conservation, climate resilience, and inclusive economic development.